PLEA BARGAINING IN REALIZING EFFECTIVE AND EFFICIENT CRIMINAL JUSTICE SYSTEMS - Widianto, Monisti Sri; Amarini, Indriati; Kartini, Ika Ariani (UMPurwokerto Law Review, 2020)
The condition of the criminal justice system is allegedly full of corrupt practices (judicial corruption), facing the problem of piles of cases that are very severe (overloaded), slow and time-consuming (waste of time), proceed with expensive costs (very expensive), less able to accommodate the sense of justice in society (unresponsive), and too rigid, formal and too technical (nonflexible, formalistic, and technically). There are two problems that will be analyzed in this study, namely First, how plea bargaining can bring about effective and efficient criminal justice. Second, how is the bargaining plea in the Criminal Procedure Code Draft? Research shows that Plea Bargaining is a faster and more efficient case resolution if the defendant pleads guilty. Not only is the guilty plea of the defendant or the lawyer able to make an agreement with the public prosecutor regarding the generally lighter form and duration of the sentence. It is necessary to regulate the mechanism of the implementation of plea bargaining system in the criminal justice process, guarantees of the rights owned by the defendant at the time of plea bargaining mechanism, as well as time limits on each stage of the examination in order to realize an effective and efficient criminal justice. Keywords: Plea Bargaining, Justice, Effective, and Efficient. Â